Knowledge and Attitude towards Basic Life Support among Health Care Professionals Working in Emergency of BPKIHS - Poudel, Masum; Bhandari, R; Giri, R; Chaudhary, S; Uprety, S; Baral, D D (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Basic Life Support (BLS) aims to maintain respiration and circulation in the cardiac arrest victim and involves a major focus on cardiopulmonary resuscitation (CPR) with minimal use of ancillary equipment. The raised standards of care demand that knowledge about BLS/ CPR be updated and include the lay persons as well as medical experts who have the potential to become the teachers of the skill. The objective of the study was to describe the knowledge and attitude of medical personnel (nurses and doctors) towards BLS/ CPR. Methods: This cross sectional study was done among the doctors and nurses working in Department of General Practice and Emergency Medicine, BPKIHS, Nepal after ethical approval. A pre-validated questionnaire (Shrestha et al, WJEM, 2012) with pre-structured questions was used for assessing the knowledge and attitude. Attitude was measured using 5 point Likert. Designation, previous training and demographics were used as describing variables. For data recording and statistical analysis; Microsoft Excel, SPSS 11 and EPI Info were used. Results: Total number of sample size was 84 medical personnel working in emergency department (consultant 12, junior resident 16, house officer 18, and senior nurse 3 and staff nurse 35). Nine (11%) respondents answered more than 10 questions, 57 (68%) answered 6-10 question and 18 (21%) answered less than 5 question. Average mean score (total 15) was 7.40 (SD 2.32, 95% CI 6.90-7.90).Mean score of the positive attitude (total 15) to CPR was 11.1807 (2.43, 10.65-11.71). The mean score for reluctance (total 5) to perform CPR was 3.25 (consultants and those who were certified in BLS or taken BEC course in the department had maximum score in knowledge (p<0.001). Higher positive attitude score to BLS/ CPR was associated with an increasing age strata (p 0.001), senior designation (p 0.001), BLS course (p 0.048) and BEC department course (p 0.009). Conclusion: Knowledge in BLS/ CPR was average. CPR/ BLS training and frequent assessments are recommended at our hospital.